Study polymorphism of ovine IGFBP-3 Gene and its association with carcass traits and fatty acids profiles in Zel sheep using PCR-SSCP - Ali Qazi Khani Shad (مجله بیوتکنولوژی کشاورزی, 2014)
IGF-1 hormone transports by connecting to IGF-binding proteins (often IGFBP-3) in the biological fluids. This protein acts as an IGF1 carrier and helps to prolong half-life of hormone and can increase or decrease biological activity of hormone on cellular surface. The purpose of the research was to study the polymorphisms of IGFBP-3 gene and its association with carcass traits and fatty acids profiles in Zel sheep as a thin-tailed breed using PCR-SSCP. In this study we used 130 Zel sheep randomly and recorded their traits measure we wanted. to determine of fatty acids, we took 6ml blood in venojects containing EDTA and immediately centrifuged them for 10 minutes by 3000g (5200 rpm) to separate the plasma. DNA was extracted from muscle tissue by Biotech company kit. Then the Polymerase chain reaction (PCR) used to amplify of 654 bp fragment of exon 3 of IGFBP-3 gene. PCR products were electrophoresed on polyacrylamide gel (method SSCP) and stained with silver nitrate method to distinguish different patterns. Results indicated the different patterns, may be due to polymorphism in this fragment. Frequency of patterns 1, 2, 3, 4 and 5 were 67/66, 33/3, 67/6, 33/13 and 10 percent respectively. Trait carcass weight (P <0.05), back fat thickness (P <0.01) and crude protein in meat (P <0.01) had significantly differences with different patterns. Significant association observed by Heptadecanoic acid (C17: 0) with different patterns of IGFBP3 gene. No other association was observed by IGFBP3 patterns with other traits and fatty acids profiles.